Youth experiences using the South African financial system - Ndlovu, Zamandlovu (Graduate School of Business (GSB), 2023)
One of the biggest challenges facing leaders and policymakers is successfully transitioning young people from education into gainful livelihoods. Reputable bodies such as the International Labour Organisation (ILO) have argued that promoting financial inclusion among young people is an important aspect of promoting their entry into the labour markets (Friedline & Rauktis, 2014). Rather than compare the experiences of the included against those who are excluded, this research explored the experiences of young people who are already included in the financial system to understand which broader social dynamics contribute towards young people's financial and social outcomes. The research took the form of a field study based on a qualitative research approach using an contextual social constructionism lens to conduct a thematic analysis to understand the experiences of young people using the South African financial system. The sample was drawn from the population of young people between the ages of 23 – 35, an age range that falls within the South African definition of youth. The 30 participants who volunteered for the study were from different cities within the Gauteng province. The research results demonstrated the increasingly large role played by the financial sector in the transition from childhood to adulthood. Through the experiences of the included youths, financial outcomes were found to result from complex interconnections between the structural, social, household, and personal attributes. The study results suggest that six interrelated dynamics contribute to young people's financial system experiences. These dynamics are parents' financial capacity, education, income/cash transfers, expectations on young people, and the social policy context. This suggests that the financial system is a social construct, impacted by public policy, global and local economic trends, and the context in which its users find themselves. Despite this, young people are not socialised within the home to deal with the realities of early and sustained usage of increasingly complex financial products. Prevailing definitions of financial inclusion are largely confined to the functioning of financial institutions. This disconnect was found to lead to incomplete recommendations from policy makers on what might improve the experiences and social outcomes of youth from lower income backgrounds. The study's findings suggestions are that programs to build people's financial skills should pay attention to the whole situation in which young people learn about money. Parents should be able to teach their kids about debt and insurance, as well as other financial products. Policies for financial inclusion need to be aware of how regressive welfare policies make it so that younger people have to carry more complicated products like student loans earlier in their lives. Financial institutions are making products that are good for young people, and regulators should pay more attention to market conduct reform to strengthen the consumer protection parts of youth-specific financial sector rules. Keywords: Youth Transitions, Financial Inclusion, Social Constructionism